Tensions Between the Resource Damage and the Private Benefits of Appropriation in the Commons - Esther Blanco; Maria Claudia Lopez; James M. Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
This study examines appropriation decisions in a linear appropriation game setting with variations in the resource damage from appropriation and simultaneous variations in the resource damage and the opportunity cost of conservation, where the ratio of these two variables is held constant. In symmetric and asymmetric group contexts, subjects make decisions without feedback from a menu of seven decision situations. In summary, individual appropriation levels are found to be inversely correlated with the ratio of marginal resource damage from appropriation to the marginal private benefit of appropriation and no significant differences are observed in individual appropriation levels across treatments where this ratio is equal. Moreover, among subjects facing the same marginal incentives, no significant differences are found between decisions of subjects in symmetric and asymmetric groups. Finally, using forecasts of others' appropriation decisions; we find evidence of both a direct effect from changes in marginal monetary incentives and an indirect effect associated with changes in subjects' first order beliefs of the appropriation decisions of others. These findings are consistent with previous evidence for public goods games supporting the relevance of the marginal per-capita return and conditional reciprocity in explaining variations in cooperation levels.
Keywords: D7; D3; C90; 330; common pool resources; asymmetry; resource damage; private benefits; laboratory experiments